A mixed problem of active aerosol pollution - Dung, Hoang Dinh (Vietnam Journal of Mechanics, 2000)
The mixed problem of active aerosol pollution is stated in the mathematical modeling of environment problems [1] and was studied by some authors (see [1], [2], [3], ...). In this work we give the solution using the theory of Schwartz distributions.